The Effect of Infrastructure Investment on Economic Growth in Rural Areas: Case Study in Papua Province - Hutajulu, Halomoan (Journal of Management, 2024)
This study examines the state of infrastructure and economic dynamics in Papua Province from 2016 to 2020, focusing on domestic investment, foreign investment, household consumption, and Gross Domestic Product (GDP). The data used comprises the value of domestic investment (Invs_DN), foreign investment (Invs_LN), household consumption (Kons_RT), and GDP for each year during the period. Descriptive analysis reveals that domestic and international investment fluctuated significantly, whereas household consumption steadily increased. GDP swings reflect the region's economic fragility.A correlation analysis reveals a very poor association between investment (both domestic and foreign) and GDP, as well as a slightly stronger but still weak relationship between household consumption and GDP. The linear regression model used to assess the impact of these variables on GDP reveals that the three variables make little contribution to explaining differences in GDP. These findings suggest that variables other than investment and household spending may have a larger impact on GDP in Papua Province. As a result, Papua Province requires more comprehensive and concentrated policies to stabilize and enhance investment, as well as discover and optimize other elements that can encourage long-term economic growth.